Linguistic Minorities and Crisis Communication: Assessing the Contribution of Real-Time Machine-Translated Instant Messaging During a Cascading Crisis - Kizito Tekwa; Jessica Jiexiu Liu (SAGE Open)
This study investigates the role of machine-translated instant messaging (IM) during a cascading crisis, taking foreigners, who constitute the linguistic minority community in China, as the participants. Informed by the information-seeking behavior theory, the study assesses the extent to which participants machine-translated pandemic-related IMs they received via WeChat, the popular IM platform in China and their perception of the quality of translated IMs. From a cultural perspective, the study evaluates the language and timing of the messages as well as the degree of integration of foreigners into the pandemic messaging apparatus. Based on data gathered via a questionnaire (430 respondents) and semi-structured interviews (15 interviewees), it was found that participants overwhelmingly machine-translated pandemic and non-pandemic-related IMs and perceived the quality to be good. In contrast, they had an unfavorable perception of the timing and tone of IMs, as well as their extent of involvement in the crisis information apparatus. Based on the findings, recommendations are proposed to better integrate members of linguistic minority communities, especially those with knowledge of the mainstream language, into crisis information management.